Sugarcane phytomass labeling with application of 15N-urea solution - Faroni, Carlos Eduardo; Trivelin, Paulo Cesar Ocheuze; Silva, Priscila Helena da; Bologna, Isabela Rodrigues; Vitti, André César; Franco, Henrique Coutinho Junqueira (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this research was to compare three methods of 15N-urea solutions application: spray on leaf, injection in the plant base stem and root immersion, in order to define the most efficient labeling sugarcane phytomass with 15N method. The experiment was carried out at APTA - Pólo Regional Centro Sul, in Piracicaba, SP, Brazil, and the sugarcane variety SP80 3280 was planted in pots filled out with approximately 120 dm3 of a Typic Quartzipsamment soil. The experiment was conducted in a completely randomized design with four replicates. There were no difference between the methods in the plant parts dry mass, in 11o development month, and their 15N abundances were superior to the natural one, being verified the following decreasing labeling order: aerial part > rhizome > rhizome + roots in the layer 0.0–0.2 m > roots in the layer 0.2––0.4 m > roots in the layer deeper than 0.4 m. Among the 15N-urea solution application methods, the injection in the base stem is the easiest to apply, the most effective in dry mass labeling and the one wich presented the largest 15N tracer recovery (96%). The spray on leaf method is comparable to the injection in the base stem only for the labeling with 15N and tracer recovery for root system.
Keywords: Saccharum spp.; aerial part; root system; isotope labeling